The baptismal episode as Trinitarian narrative : proto-trinitarian structures in Mark's conception of God - Mortensen, Hallur, 1981- (Mohr Siebeck, 2020)
Hallur Mortensen analysiert den Gottesbegriff bei Markus, indem er die Verbindung der Taufe in 1,9-11 zum Kommen des Herrn, zum Evangelium und zum Reich Gottes in 1,2-3 und 1,14-15 betont. Die göttliche Stimme, die die Identität von Jesus und Gott offenbart, und der Geist werden im Kontext des jüdischen Monotheismus untersucht.
Description based upon print version of record.
Based on the author's thesis (doctoral)--Durham University, 2018.
Keywords: Jesus Christ -- Baptism.; Bible. -- Mark -- Criticism, interpretation, etc.; Bible. -- Psalms -- Quotations in the New Testament.; Bible. -- Isaiah -- Quotations in the New Testament.; Jésus-Christ -- Baptême.; Jesus Christ; Bible. -- Isaiah; Bible. -- Mark; Bible. -- Psalms; Trinity -- Biblical teaching.; Trinité -- Enseignement biblique.; Baptism of Jesus Christ; Trinity -- Biblical teaching; Criticism, interpretation, etc.; Quotations